2022
DOI: 10.3390/life12071099
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 in Regulating Radiation Responses

Abstract: p53 is known as the guardian of the genome and plays various roles in DNA damage and cancer suppression. The p53 gene was found to express multiple p53 splice variants (isoforms) in a physiological, tissue-dependent manner. The various genes that up- and down-regulated p53 are involved in cell viability, senescence, inflammation, and carcinogenesis. Moreover, p53 affects the radioadaptive response. Given that several studies have already been published on p53, this review presents its role in the response to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 204 publications
(217 reference statements)
2
9
0
Order By: Relevance
“…Nodes with a high degree, also known as hubs, are more likely to play an essential role (He and Zhang, 2006). In line with this, multiple review articles have described the key role of MDM2 in the p53-MDM2-signaling axis as part of the DDR (Nag et al, 2013;Haronikova et al, 2019;Gnanasundram et al, 2021;Okazaki, 2022). In addition, we found that MDM2 is targeted by 44 different miRNAs.…”
Section: Figuresupporting
confidence: 76%
“…Nodes with a high degree, also known as hubs, are more likely to play an essential role (He and Zhang, 2006). In line with this, multiple review articles have described the key role of MDM2 in the p53-MDM2-signaling axis as part of the DDR (Nag et al, 2013;Haronikova et al, 2019;Gnanasundram et al, 2021;Okazaki, 2022). In addition, we found that MDM2 is targeted by 44 different miRNAs.…”
Section: Figuresupporting
confidence: 76%
“…In cells, the phosphorylation of H2AX at its serine 139 residue (rH2AX) and the activation of p53 are crucial responses to DNA damage caused by radiation, particularly double-strand breaks [ 62 , 63 , 64 ]. These responses aid in the repair of damaged DNA or remove cells with significant damage through apoptosis [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genetic instability is one of the most striking features of malignant tumours, however, P53 plays an important role for detecting DNA damage and repairing the genome. When p53 responds to DNA damage, it triggers either cell cycle arrest or apoptosis (Okazaki, 2022). Radiotherapy destroys cancer cells via DNA damage; DNA damage is causing increase in p53 expression via ATM kinase activation (Cui et al, 2022).…”
Section: Discussionmentioning
confidence: 99%